ACUTE TOXICITY OF CADMIUM TO SIX INTERTIDAL INVERTIBRATES - MOHAN, C V; MENON, N R; GUPTA, T R.C (Fishery Technology, 2017)
Following a static bioassay techniques the acute toxicity of cadmium to six species of intertidal invertebrates was determined. The sensitivity of the animals to cadmium was of the following order. Emerita sp. (burrowing crustacean) Donax spiculum (burrowing bivalve) Perna viridis (sedentary bivalve) Sabellaria clandestinus(tube-dwelling polychaete) Modiolus carvalhoi and Modiolus sp. (sedentary bivalves). The above observation was based on the median lethal concentrations recorded for the different species, Emerita sp. 1.35 p.p.m., Donax spiculum 1.8 p.p.m., Perna viridis 2.5 p.p.m., Sabellaria clandestinus 2.8 p.p.m., Modiolus carvalhoi 5.6 p.p.m. and Modiolus. sp. 9.6 p.p.m. The findings throw insight into the toxicity of cadmium to the common intertidal animals which are either suspension or detritus feeders.